Identification of hexosamine biosynthesis pathway as a novel prognostic signature and its correlation with immune infiltration in bladder cancer - Cui, Yangyan; Feng, Hanyi; Liu, Jiakuan; Wu, Jiajun; Zhu, Rujian; Huang, Ruimin; Yan, Jun (Frontiers in Molecular Biosciences, 2022)
Background: Urinary bladder cancer (UBC) is one of the common urological malignancies, lacking reliable biomarkers to predict clinical outcomes in UBC patients. Thus, it is needed to identify the novel diagnostic/prognostic biomarkers to stratify the high- risk UBC patients. As a shunt pathway of glycolysis, the hexosamine biosynthesis pathway (HBP) has been implicated in carcinogenesis. However, its prognostic value in UBC remains unclear. Methods: The RNA sequencing and mRNA microarray datasets were downloaded from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus databases. The expression levels of five HBP genes were analyzed in normal and UBC samples, and their associations with stage, grade and survival were plotted. The performance of HBP risk group was evaluated by receiver-operating characteristics (ROC) curve. The HBP signature was generated by Gene Set Variation Analysis (GSVA) and its association with clinicopathological parameters and survival were analyzed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were carried out to examine the potential biological functions of HBP using DAVID online tool. The infiltration estimation fraction of immune cells was performed using CIBERSORT-ABS algorithm. Gene set enrichment analysis (GSEA) was used to explore the potential function of HBP in tumor immunoregulation. Results: Four HBP genes were upregulated in UBCs compared to normal tissues in TCGA-BLCA dataset. The upregulation of all five HBP genes was significantly associated with tumor grade and stage of UBC in three independent UBC datasets. The expression of HBP genes predicted poor clinical outcomes in UBC patients in both TCGA-BLCA and GSE13507 datasets. The high-risk group based on HBP genes showed a poor prognosis. Furthermore, HBP signature was positively associated with tumor grade and stage in TCGA-BLCA dataset and with tumor grade, stage, distal metastasis and poor survival in GSE13507 dataset. Interestingly, high-HBP signature group exhibited a high infiltration of immune cells, particularly the macrophage population. Conclusion: We identified that HBP was a promising prognostic biomarker in UBC patients and strongly associated with immune infiltration.